Disruption of actin dynamics induces autophagy of the eukaryotic chaperonin TRiC/CCT - Date, Yuki; Matsuura, Akira; Itakura, Eisuke (Cell death discovery, 2022)
Autophagy plays important role in the intracellular protein quality control system by degrading abnormal organelles and proteins, including large protein complexes such as ribosomes. The eukaryotic chaperonin tailless complex polypeptide 1 (TCP1) ring complex (TRiC), also called chaperonin-containing TCP1 (CCT), is a 1-MDa hetero-oligomer complex comprising 16 subunits that facilitates the folding of ~10% of the cellular proteome that contains actin. However, the quality control mechanism of TRiC remains unclear. To monitor the autophagic degradation of TRiC, we generated TCP1α-RFP-GFP knock-in HeLa cells using a CRISPR/Cas9-knock-in system with an RFP-GFP donor vector. We analyzed the autophagic degradation of TRiC under several stress conditions and found that treatment with actin (de)polymerization inhibitors increased the lysosomal degradation of TRiC, which was localized in lysosomes and suppressed by deficiency of autophagy-related genes. Furthermore, we found that treatment with actin (de)polymerization inhibitors increased the association between TRiC and unfolded actin, suggesting that TRiC was inactivated. Moreover, unfolded actin mutants were degraded by autophagy. Taken together, our results indicate that autophagy eliminates inactivated TRiC, serving as a quality control system.